Innate immune pathway activated mesenchymal stromal cells improve function and histologic outcomes in a rodent osteoarthritis model - Plaisance, Cody; Chow, Lyndah; Impastato, Renata; Williams, Zoë J.; Sabino, Isabella; Sikes, Katie J.; Santangelo, Kelly S.; Dow, Steven; Pezzanite, Lynn M. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionIntra‐articular administration of mesenchymal stromal cells (MSC) has demonstrated anti‐inflammatory and chondroprotective activity in both preclinical models and in randomized clinical trials in patients with osteoarthritis (OA). Nonetheless, precedent from MSC studies in non‐OA models suggests that the overall anti-inflammatory effectiveness of MSC can be improved by prior immune activation through cytokines or innate immune pathways.MethodsTherefore, in the current study, we determined whether activation of MSC by two different innate immune pathways (Toll‐like receptor 3 (TLR3) pathway or Stimulator of Interferon Genes (STING) pathway could improve their effectiveness for intra‐articular treatment of OA, using a murine destabilization of the medial meniscus (DMM) model. Outcome parameters included voluntary gait activity, joint histology and RNA transcriptomic analyses of synovial tissues.ResultsWe found that activation of MSC via either innate immune pathway improved functional voluntary movement outcomes compared to treatment with non-activated MSC. Moreover, cartilage integrity, including cartilage preservation, was significantly improved in mice receiving activated MSC, with greater benefits observed in animals treated with STING pathway-activated MSC compared to animals treated with non‐activated MSC alone. Transcriptomic analysis of joint tissues revealed that treatment with activated MSC upregulated pathways associated with tissue remodeling, angiogenesis, and wound healing compared to tissues from animals treated with non-activated MSC.DiscussionThese findings indicate therefore that innate immune activation of MSC prior to intra‐articular delivery for treatment of OA can significantly improve functional gait activity and chondroprotective effects compared to non‐activated MSC and suggest that this strategy could be evaluated clinically.